Kadar Nafkah Perspektif Imam Empat Madzhab - Umami, Hafidhul; Zakiya, Lailatuz (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
This research focuses on the determination of nafkah (maintenance) from the perspectives of the four major Islamic schools of thought: Hanafi, Maliki, Shafi'i, and Hanbali. Nafkah refers to the financial and material obligations that a husband must fulfill for his wife, including necessities such as food, clothing, housing, and other living expenses. While all four madhhabs agree on the obligation of nafkah, they differ in determining its amount, which is influenced by the husband’s financial capacity, the wife’s social standing, and prevailing local customs. The Hanafi school emphasizes the wife’s social status and the economic conditions of the husband in determining the nafkah. The Maliki perspective prioritizes the customary standards of living within the community. The Shafi’i school considers both the financial capability of the husband and the wife’s needs. Meanwhile, the Hanbali school balances the husband’s financial means with the wife’s requirements. This study aims to analyze these differences and their underlying principles by referencing primary sources, such as the Qur’an, Hadith, and classical fiqh literature. Understanding these variations offers valuable insights for applying nafkah obligations in contemporary contexts while adhering to Islamic jurisprudence.